Changes in Exposure to Secondhand Smoke Among Youth in Nebraska, 2002-2006 - Lazarous Mbulo, PhD (Centers for Disease Control and Prevention, 2008)
IntroductionSecondhand smoke is a major cause of morbidity and mortality. It has been associated with serious health problems in both children and adults. Efforts to reduce exposure to secondhand smoke in Nebraska have included programs to prevent tobacco use among young people and campaigns for smoke-free workplaces and homes. Despite these interventions, young people continue to be exposed to secondhand smoke at an unacceptably high rate. The objective of this study was to examine the extent to which Nebraska public middle and high school students were exposed to secondhand smoke in 2002 and 2006, to evaluate factors associated with this exposure, and to propose interventions.MethodsThe Nebraska Youth Tobacco Survey was administered in 2002 and 2006 to a representative sample of students from public middle and high schools. All students who chose to participate completed an anonymous, self-administered survey that included questions on demographics, tobacco use, tobacco-related knowledge and attitudes, and exposure to secondhand smoke. Data were weighted to account for nonresponses at both student and school levels and to ensure generalizability of the estimates for public school students in Nebraska according to their grade, sex, and race/ethnicity. This study analyzed a subset of responses on secondhand smoke exposure, which was defined as being in a room or vehicle during the previous 7 days with someone who was smoking cigarettes.ResultsSecondhand smoke exposure in a room, a vehicle, or both declined significantly among all students from 2002 (69.0%) to 2006 (61.3%). In both 2002 and 2006, students were significantly more likely to be exposed to secondhand smoke in a room than in a vehicle (64.4% vs 48.2% in 2002 and 56.9% vs 40.2% in 2006). Among racial and ethnic groups, only white students experienced a significant decline in exposure from 2002 (70.0%) to 2006 (61.4%). Girls were significantly more likely to be exposed to secondhand smoke in 2006 than were boys, and only boys experienced a significant overall decline in exposure from 2002 (69.3%) to 2006 (57.7%). Smoking behaviors and attitudes continued to influence secondhand smoke exposure from 2002 to 2006, although students experienced significant declines whether they were smokers or nonsmokers, and whether they lived with a smoker or not. Those with close friends who smoked and those who did not perceive secondhand smoke as harmful, however, did not benefit.ConclusionsThese data indicate reductions in exposure to secondhand smoke among Nebraska's middle and high school students, but exposure remains a problem, particularly in rooms. Adoption of a comprehensive statewide smoke-free policy will contribute to significantly reduced exposure to secondhand smoke among young people in public places, but other measures to address exposure in the home and private vehicles are needed or should be strengthened. These include physician counseling based on behavioral change theory to encourage cessation and home-based no-smoking rules, in addition to interventions that target minorities, who are disproportionately affected by secondhand smoke exposure. Evaluation of existing measures, such as programs to prevent tobacco use among young people and campaigns to collect pledges for smoke-free homes, will be required to determine their effectiveness in reducing exposure to secondhand smoke among youth in Nebraska.